Serum 25-Hydroxyvitamin D Concentrations at Birth in Children Screened for HLA-DQB1 Conferred Risk for Type 1 Diabetes - Marjaana Mäkinen; Eliisa Löyttyniemi; Maarit Koskinen; Mari Vähä-Mäkilä; Heli Siljander; Mirja Nurmio; Juha Mykkänen; Suvi M Virtanen; Olli Simell; Heikki Hyöty; Jorma Ilonen; Mikael Knip; et al. (ENDOCRINE SOC, 2022)
Context: Vitamin D has several effects on the immune system that might be of relevance for the pathogenesis of type 1 diabetes (T1D).Objective: To evaluate whether umbilical cord serum concentrations of 25-hydroxy-vitamin D (25[OH]D) differ in children developing either islet autoimmunity (IA) or overt T1D during childhood and adolescence.
Design: Umbilical cord serum samples from 764 children born from 1994 to 2004 with HLA-DQB1 conferred risk for T1 D participating in the Type 1 Diabetes Prediction and Prevention Study were analyzed for 25(OH)D using an enzyme immunoassay.
Setting: DIPP clinics in Turku, Oulu, and Tampere University Hospitals, Finland.
Participants: Two hundred fifty children who developed T1D diabetes at a median age of 6.7 years (interquartile range [IQR] 4.0 to 10.1 years) and 132 additional case children who developed IA, i.e., positivity for multiple islet autoantibodies. Cases were matched for date of birth, gender, and area of birth with 382 control children who remained autoantibody negative. The median duration of follow up was 9.8 years (IQR 5.7 to 13.1 years).
Main Outcome Measure: The median 25(OH)D concentrations.
Results: The median 25(OH)D concentration in cord serum was low [31.1 nmol/L (IQR 24.0 to 41.8); 88% <50 nmol/L], but not statistically different between children who developed T1D or IA and their control groups (P = 0.70). The levels were associated mainly with geographical location, year and month of birth, age of the mother, and maternal intake of vitamin D during pregnancy.
Conclusions: The 25(OH)D concentrations at birth are not associated with the development of T1D during childhood.